A PEM Fuel Cell Diagnostic System Using the Extension Theory - Chin-Tsung Hsieh; Meng-Hui Wang; Ying-Piao Kuo (International Journal of Distributed Sensor Networks)
Composed of a single proton exchange membrane fuel cell (PEMFC), a sensor module, and a ZigBee wireless communication module, a fault diagnostic system is proposed in this work to monitor the operation of a fuel cell system. Accordingly, such quantities as cell's output voltage, current, operating temperature, and pressures of gases supplied are monitored. Subsequently, an extension matter-element model is built according to malfunctions of the fuel cell system, which are further categorized into 7 types, each with 12 sorts of characteristics. An extension evaluation method is then directly applied to diagnose such fuel cell system. A human machine interface built under LabVIEW 2009 is incorporated in such a way that a fault(s) can be detected and fixed in a timely manner such that the life cycle of such fuel cell system can be extended.